Stratigraphic architecture, paleogeography and provenance of the cenozoic sedimentary rocks in southern perú (Tacna, 18° s) . [Arquitectura estratigráfica, paleogeografía y proveniencia sedimentaria de las rocas cenozoicas del sur de perú (Tacna, 18° s)] - Alván A.A. (2020)
The Cenozoic rocks lying in the Province of Tacna (18° S), southern Perú, represent approximately 600 m of stratigraphic thickness. This stacking groups the Sotillo (Paleocene), Moquegua Inferior (Eocene), Moquegua Superior (Oligocene), Huaylillas (Miocene) and Millo formations (Pliocene), and these are the sedimentary fill of the Moquegua Basin. The sediments of the three latter formations are organized into nine sedimentary facies and five architectural elements. Their facies associations suggest the existence of an ancient highly channelized multi-lateral fluvial braided system, with upward increase of pyroclastic and conglomeratic depositions. The heavy mineral spectra make each lithostratigraphic unit unique and distinguishable, being the sediments of the Moquegua Superior Formation rich in garnets, titanites and zircons; while the sediments of the Huaylillas and Millo formations in clinopyroxenes. This mineral arrangement becomes an excellent tool for stratigraphic correlations between outcrops and subsurface stratigraphy (by means of well cores studies) and allow to sketch out a new stratigraphic framework and a complex of rocky blocks bounded by normal faults, often tilted. The sediment mineralogy also suggests that the rocks conforming the Western Cordillera were the main source of sediments for the Moquegua Basin in Tacna. In this context, the detritus of the Moquegua Superior Formation derives mainly from the erosion of the rocks forming the Coastal Basal Complex (Proterozoic), the Ambo Group (Carboniferous) and the Junerata/Chocolate Formation (Early Jurassic). The Huaylillas Formation is a pyroclastic and sedimentary unit which components derived mainly from the Huaylillas volcanism (Miocene) and partly from the denudation of the Toquepala Group (Late Cretaceous). The Huaylillas Formation widely contrasts to the underlying Moquegua Superior Formation due its mineralogy and facies. Finally, the detritus of the Millo Formation derived mostly from the rocks forming the Barroso Formation (Pliocene), and their facies represent a higher contrast in relation to the underlying units due its notorious conglomerate facies. © INRA and Springer-Verlag France 2015.